The Regional Partnership Program in Jumantono Sub-District, Karanganyar Regency - Muhtadi, Muhtadi; Rauf, Rusdin; Sarbini, Dwi; Rustiono, Dedy (Journal of Community Services and Engagement, 2018)
Jumantono Subdistrict, Karanganyar Regency is an area that has been developed as a center for livestock and agriculture in Karanganyar Regency. The most dominant agricultural and plantation products from Jumantono sub-district are cassava and durian. The Regional Partnership Program (PKW) activities in Jumantono sub-district are focused on two fields, namely First, agriculture and animal husbandry, handling the environment due to animal odor and feces, through the application of clean livestock by utilizing biogas installations which can also be used for cheap household energy sources, and production of organic fertilizers that can be utilized in agricultural and plantation activities. Second, for fields based on economic aspects, it is directed to elevate the potential of local Jumantono plants, namely cassava and durian. Potential of cassava will be developed starting from the aspect of cultivation with the selection of good cassava seeds and the development of grafting cassava which can provide an average yield of 30-70 kg / tree. This paper reports on the PKW activities in Jumantono that were carried out in March d November 2018, specifically about skills in production and development of business based on cassava processing and other products by SMEs in Jumantono. Partners of PKK groups in Ngunut and Kebak villages, after being taught how to cultivate and maintain cassava, were then trained on the manufacture of various processed cassava. The mentoring process carried out on partners starts from the way of making Mocaf flour, various processed cassava and about the packaging design of cassava processed products. The expected output of this PKW activity is the realization of more productive agriculture or cassava cultivation and diversification of various cassava-based processed products. Improvements in the appearance of labels and packaging, as well as the development of marketing products from Ngunut and Kebak villages have also been carried out in this PKW activity.